FAKTOR-FAKTOR YANG MEMPENGARUHI PELAKSANAAN KINERJA SIREKAP DALAM MENDUKUNG PILKADA BERINTEGRITAS DI KABUPATEN KENDAL - Rizky Ananda Putra; Muhammad Fatchuriza (Halu Oleo University, 2025)
In the 2024 simultaneous elections, the implementation of Sirekap caused various polemics. At least 11,233 polling stations were recorded as unable to access the Sirekap application. The purpose of this writing is to Analyze the Factors that Influence the Implementation of Sirekap Performance in Supporting Integrity-Based PILKADA in Kendal Regency. While the type of research is qualitative research. The technique that will be used in determining informants is purposive sampling through key persons. The data collection techniques used by the researcher are observation, interviews and documentation. Based on the results of the study, it show that the implementation of the Sirekap application in Kendal Regency by the Kendal Regency KPU and the Adhoc body has been going quite well. although in terms of communication it is not so good because there is no delivery of information to the public regarding Sirekap because it is a personal tool of the KPU. while from other factors it is quite good. The implementation of the Sirekap Application in the 2024 Simultaneous Election Vote Recapitulation in Kendal Regency as a whole has gone as well as it should. However, it is not yet optimal because in its implementation there are still technical obstacles that slightly hinder the Sirekap operator. for this reason, there needs to be a clear policy regarding the Sirekap target so that its delivery can be comprehensive to the Community.